2009
DOI: 10.3844/jssp.2009.177.182
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Marketing Orientation Concept in Jordanian Service Industry

Abstract: Problem statement:The objective of this study was to explore the extent to which the concept of marketing orientation was clear and adopted by Jordanian service firms, focusing on the financial sector. Approach: Based on an empirical fieldwork. Results: The study concluded that the majority of Jordanian financial service firms had a misconception of marketing orientation concept. They believed that they exercise marketing orientation concept, while their actual practice of selling orientation. Conclusions: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Market orientation as a driver of SMME service business performance has attracted scholarly interests as others question its relevance (Walsh and Lipinski, 2009). In an empirical study conducted on service SMMEs in Jordan, the findings revealed that the concept of MO is not clear and not adopted by most of the Jordanian service SMMEs (Ismail et al, 2009).…”
Section: Market Orientation In Service Smmes In Botswanamentioning
confidence: 99%
“…Market orientation as a driver of SMME service business performance has attracted scholarly interests as others question its relevance (Walsh and Lipinski, 2009). In an empirical study conducted on service SMMEs in Jordan, the findings revealed that the concept of MO is not clear and not adopted by most of the Jordanian service SMMEs (Ismail et al, 2009).…”
Section: Market Orientation In Service Smmes In Botswanamentioning
confidence: 99%